Association between body mass index and outcomes after percutaneous coronary intervention in multi-ethnic south east Asian population: A retrospective analysis of the Malaysian National Cardiovascular Disease Database - percutaneous coronary intervention (NCVD-PCI) registry / Zaid Azhari - Zaid, Azhari (2017)
Objective: The state of being obese has been generally associated with worse outcomes in many clinical conditions. However, it has been shown in certain settings that obesity might be protective and had better outcomes, and this phenomenon is called "obesity paradox". This study was conducted to examine the relationship between body mass index (BMI) and outcomes after percutaneous coronary intervention (PCI) in a multi-ethnic South East Asian population. Methods: This is a retrospective study of anonymized data obtained from the Malaysian National Cardiovascular Disease Database - Percutaneous Coronary Intervention (NCVD-PCI) registry. 28,742 patients from the NCYD-PCl registry who had their first PCI between January 2007 and December 2014 were included. Those without their body mass index (BMI) recorded or BMI less than 11 kg/m2 or more than 70 kg/m2 were excluded. The patients were divided according to their BMI group , and their baseline characteristics, angiographic profiles and medications upon disharge were compared. In-hospital death, major adverse cardiovascular events (MACE), and vascular complication between different BMI groups were also calculated. Results: The patients were divided into four groups; underweight (BMI <18.5 kg/m2), normal BMI (BMI 18.5 to >23 kg/m2), overweight (BMI 23 to <27.5 kg/m2) and obese (BMI >27.5 kg/m2). Comparison of their baseline characteristics showed that the obese group was younger, had lower prevalence of smoking but higher prevalence of diabetes, hypertension, and dyslipidemia.Obese patients were more likely to have multi-vessel disease, but lesser involvement of the Left Anterior Descending (LAD) artery. There was no difference found in terms of in-hospital death, MACE and vascular complications after PCI. multivariable Cox proportional hazard regression analysis showed that compared to normal BMI group, the underweight group had a non-significant difference (HR: 1.02, p=0.952), while the overweight group had significantly lower risk of 1-year mortality (HR:0.71, p=0.005). The obese group also showed lower HR but this was non-significant (HR: 0.78, P=0.056). Conclusion: Using Asian specific BMI cut-off points, the overweight group in our study population was independently associated with lower risk of 1-year mortality afler PCI compared to the normal BMI group.